Peran Pemerintah Daerah Dalam Penyelesaian Konflik Antara Transportasi Konvensional dan Transportasi Online (Studi Pada Dinas Perhubungan Kota Malang) - Trisna, Andri; Muluk, M. R. Khairul (Jurnal Ilmiah Administrasi Publik, 2018)
The entry of online transportation phenomenon in Malang City has caused conflict to conventional transportation. This is because there is no regulation governing the phenomenon of online transportation. In fact, the role of government as a provider of public facilities for the community, including protecting their rights from influence of corporate monopoly. However, at the local government level, there is limited authority in the law. 23 of 2014 on Regional Government. Thus, local need strong legal force to resolve transportation conflicts in Malang. This study used qualitative descriptive governments method focusing on analysis of local government role in conflict resolution between conventional transportation and online transportation through Howlett and Ramesh Policy Instruments. The results of this study that the Government of Malang is more inclined towards the Compulsory Instrument by applying PM No.108 Year 2017 as the legal basis in resolving the conflict between conventional transportation and online transportation in Malang.Â Â Â